COMMUNICATION BARRIER ENCOUNTERED BY EMPLOYEES WORKING IN HOTEL INDUSTRY - A, ARUN; X, Disilva (Advances in Social Sciences Research Journal, 2017)
Objective: Communication in English is an important antecedent for a noteworthy work performance in hospitality industry. English has been considered the universal language, an employee into hospitality sector is expected to be more communicative in English language to service guest with no geographic bounds and coordinate immigrant employees from any part of the world. The study discusses the barriers and the importance of English communication skill among the employees into food and beverage outlets in hotel Industry. Method: A systematically structured questionnaire is used as a survey tool for the study to bring out the barriers of communication in English and effective measure to overcome the barriers. The advantages of an effective communication in enhancing the guest service and to maintain a cultured work environment is discussed. SPSS (21.0) statistics analysis software is used to analyze and interpret the data. Finding: An employee’s personal attributes education level psychological factors acts as the barriers for communication in English these factors are interrelated. Conclusion: The study conclude that regular training and practice sessions are required even more effectively to the employees to develop their communication and grow higher in their carrier.